Organizational attractiveness and prospective applicant's intentions to apply - Gomes, D. R.; Neves, J. (Personnel Review, 2011)
Purpose - This paper aims to clarify the process that leads prospective applicants to apply for a job vacancy when one is being evaluated. It proposes that prospective applicants evaluate a job vacancy based on the characteristics of the job and the organizational attributes. This will determine organizational attractiveness perception, and will result in the intention to apply for a job vacancy. Design/methodology/approach - An adapted employment ad that described a job and an organization were presented to 51 marketing professionals and to 73 undergraduate marketing students, who were asked to respond to a questionnaire that contained the measures of the study variables. The hypotheses were tested using linear regression methodology. Findings - Organizational attractiveness fully mediates the relations between the job characteristics and the organizational attributes with intention to apply for a job vacancy. Analysis over the compared importance of each factor has outlined the major importance of the organizational attributes and feedback of the job for determining this process. Research limitations/implications - Future research should clarify the role of organizational image as an employer and organizational familiarity in this process. Practical implications Recruitment messages in employment ads should place preferential focus on the elements of organization attributes and feedback of the job. These elements will more strongly determine attractiveness perception, and consequentially, predict intention to apply to a job vacancy. Originality/value - The study clarifies the role of organizational attractiveness in the process that leads to intention to apply for a job vacancy. A significant part of the proposed model was based on clues retrieved from existing research.